2018
DOI: 10.26719/2018.24.6.522
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care provided to children with cerebral palsy, Alexandria, Egypt

Abstract: There is a wide gap between the actual care provided to children with cerebral palsy and the recommended standards. Moreover, the documentation system in the hospital is poor. A quality improvement plan is needed for the provision of care to children with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…This result makes CP the most widespread cause of childhood disability. The prevalence of cerebral palsy is around 1.5-3 per 1 000 live births in both developed and developing countries .A study in Al-Quseir City, Red Sea Governorate reported a prevalence in children of 3.06 per 1 000 live births (2)…”
Section: Prevalencementioning
confidence: 99%
“…This result makes CP the most widespread cause of childhood disability. The prevalence of cerebral palsy is around 1.5-3 per 1 000 live births in both developed and developing countries .A study in Al-Quseir City, Red Sea Governorate reported a prevalence in children of 3.06 per 1 000 live births (2)…”
Section: Prevalencementioning
confidence: 99%
“…This is a pioneering study in Latin America, given that, when reviewing the existing literature, there are currently no studies of this type in Latin American society that reflect this problem from the point of view of caregivers of children with any type of disability. References were found in other countries [17][18][19][20] such as Cambodia [19] (whose level of development may be similar to the situation in Bolivia, although they are culturally very different). Therefore, the findings obtained in the former study should not be extrapolated to Bolivian society.…”
Section: Discussionmentioning
confidence: 90%
“…Descriptive statistics of mean ± standard deviation (SD) and frequency was carried out to calculate the measured variables. Test-retest, intra-rater, and inter-rater reliability were expressed as intra-class correlation coefficients, ICC (2,1). Repeated measurements by the same rater on real-time measurement (T1-T2) of TUDS test were used to calculate test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of functional impairment in children is CP. In school-aged children, it accounts for 60% of severe motor impairments [2]. During infancy or the preschool years, signs and symptoms of CP arise.…”
Section: Introductionmentioning
confidence: 99%